Can etanercept treatment failure in moderate-to-severe psoriasis be overcome by addition of low-dose methotrexate? A single-center experience. (3rd October 2018) - Sherman, Shany; Hodak, Emmilia; Pavlovsky, Lev
Abstract: Background: Loss of efficacy is a major anticipated shortcoming of utilizing etanercept and other biologic agents for treating moderate-to-severe psoriasis. Purpose: To investigate the addition of low-dose methotrexate as a means to increase etanercept drug survival. Methods: Eleven patients with severe psoriasis were switched to a combination of etanercept with low-dose methotrexate therapy, after a primary or secondary failure with etanercept treatment as a monotherapy. Time period for cessation of combined treatment and side effects were documented. The effect of previous methotrexate treatment was investigated. Results: Six men and five women were included in the study. The patients had moderate-to-severe psoriasis with a mean baseline Psoriasis Area and Severity Index (PASI) of 29 (median 25). Median duration of etanercept monotherapy was 12 months. Median duration of combined treatment was 13 months. Combined treatment was discontinued in three patients due to side effects. Previous failure of methotrexate monotherapy did not alter the duration of the combined treatment. Conclusion: Addition of low-dose methotrexate may rescue etanercept therapy after failure of etanercept monotherapy in patients with moderate-to-severe psoriasis.